Action of Administered Ciliary Neurotrophic Factor on the Mouse Dorsal Vagal Complex - Senzacqua, Martina; Severi, Ilenia; Perugini, Jessica; Acciarini, Samantha; Cinti, Saverio; Giordano, Antonio (Frontiers in Neuroscience, 2016)
Ciliary neurotrophic factor (CNTF) induces weight loss in obese rodents and humans through activation of the hypothalamic Jak-STAT (Janus kinase-signal transducer and activator of transcription) signaling pathway. Here, we tested the hypothesis that CNTF also affects the brainstem centers involved in feeding and energy balance regulation. To this end, wild-type and leptin-deficient (ob/ob and db/db) obese mice were acutely treated with intraperitoneal recombinant CNTF. Coronal brainstem sections were processed for immunohistochemical detection of STAT3, STAT1, STAT5 phosphorylation and c-Fos. In wild-type mice, CNTF treatment for 45 min induced STAT3, STAT1, and STAT5 phosphorylation in neurons as well as glial cells of the area postrema; here, the majority of CNTF-responsive cells activated multiple STAT isoforms, and a significant proportion of CNTF-responsive glial cells bore the immaturity and plasticity markers nestin and vimentin. After 120 min CNTF treatment, c-Fos expression was intense in glial cells and weak in neurons of the area postrema, it was intense in several neurons of the rostral and caudal solitary tract nucleus (NTS), and weak in some cholinergic neurons of the dorsal motor nucleus of the vagus. In the ob/ob and db/db mice, Jak-STAT activation and c-Fos expression were similar to those induced in wild-type mouse brainstem. Treatment with CNTF (120 min, to induce c-Fos expression) and leptin (25 min, to induce STAT3 phosphorylation) demonstrated the co-localization of the two transcription factors in a small neuron population in the caudal NTS portion. Finally, weak immunohistochemical CNTF staining, detected in funiculus separans and meningeal glial cells, matched the modest amount of CNTF found by RT-qPCR in micropunched area postrema tissue, which in contrast exhibited a very high amount of CNTF receptor. Collectively, the present findings show that the area postrema and the NTS exhibit high, distinctive responsiveness to circulating exogenous and, probably, endogenous CNTF.